Alpha-Linolenic Acid-Enriched Butter Promotes Fatty Acid Remodeling and Thermogenic Activation in the Brown Adipose Tissue - You, Mikyoung (Nutrients, 2020)
Supplementation with n-3 long-chain (LC) polyunsaturated fatty acids (PUFA) is known to promote thermogenesis via the activation of brown adipose tissue (BAT). Agricultural products that are biofortified with α-linolenic acid (ALA), the precursor of n-3 LC PUFA, have been launched to the market, but their impact on BAT function is unknown. This study aimed to evaluate the effects of ALA-biofortified butter on lipid metabolism and thermogenic functions in the BAT. C57BL/6 mice were fed a high-fat diet containing ALA-biofortified butter (n3Bu, 45% calorie from fat) for ten weeks in comparison with the isocaloric high-fat diets prepared from conventional butter or margarine. The intake of n3Bu significantly reduced the whitening of BAT and increased the thermogenesis in response to acute-cold treatment. Also, n3Bu supplementation is linked with the remodeling of BAT by promoting bioconversion into n-3 LC PUFA, FA elongation and desaturation, and mitochondrial biogenesis. Taken together, our results support that ALA-biofortified butter is a novel source of n-3 PUFA, which potentiates the BAT thermogenic function.